Making time to care differently for food: The case for the Armidale Food School - Hamilton, Jennifer Mae; Larder, Nicolette (Critical Studies in Teaching and Learning, 2023)
This paper provides the scholarly rationale for the proposed Armidale Food School (AFS) in terms of investigating care’s role in the future of learning. We use Maria Puig de la Bellacasa’s influential study of care and environment to ground the analysis. Puig (2017) argues that undoing the ecological and social harms of the agri-food system requires time to tend to plants and soil in different and slower ways. We argue that making time for these ideal forms of ecological care is difficult in the new ‘asset’ economy. Time is used up working in office jobs to service increasing financial burdens of education and mortgage debt. Grounded in traditions of radical and anti- colonial pedagogy and postcapitalist politics, AFS teaches students to think in expansive, critical, and practical ways about the barriers to these ideal forms of care while seeding changes in social practice in relation to the food system.